An engineering failure criterion for rock - Lemanza, Willy; Prinzl, Frediric; Yudhbir; Tomiolo, Andrea; Government of Japan (Bangkok : Asian Institute of Technology, 1982)
This work is concerned with the investigation of the variation with confining pressure of the failure strength of rock-like materials which simulate soft intact rock, disintegrate rock and rock containing discontinuities with varying surface roughness. The laboratory tests involve uniaxial tests , Brazilian tests, triaxial test s under varying confining stresses and direct shear tests under varying normal s tresses on soft rock like material. These results are interpreted to examine the range of applicability of the brittle failure criteria suggested by Hook & Brown (1980) to delineate the stress range where the transition from brittle to ductile rock deformation behavior takes place and to investigate the effect of the degree of disintegration and surface roughness on the failure strength criteria. From this study a new engineering failure criterion which covers whole stress range, from brittle to ductile con6it ion, of rock and rock masses was developed. Also the influence of " the degree of joint roughness" to "fracture transition stress" was studied and the relationship of them was discovered.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Strength of materials; Rock mechanics